Characteristics of fruit and vegetable MSMEs in Ethiopia: Case of Addis Ababa and Ziway/Batu - Mekonnen, Daniel Ayalew; Galema, Sophie; Nguyen, Trang; Berkhout, Ezra D. (International Food Policy Research Institute, 2023)
This study documents the characteristics and functioning of fruit and vegetable (FV) value chains in select places in Ethiopia. The case study employed a mixed methods approach, including a survey of 340 FV traders, six focus group discussions (FGDs), and analysis of the policy environment with respect to food and nutrition, the business climate, and the role of micro, small, and medium enterprises (MSMEs) in delivering safe, affordable, and nutritious foods to consumers. Among the nine types of actors that participate in the FV market and were interviewed, the majority (more than 73 percent) were retailers operating either within or outside of wet markets.